SISTEM PENILAIAN PRESTASI KERJA PEGAWAI NEGERI SIPIL PENGARUHNYA TERHADAP KEPUASAN KERJA DI INSPEKTORAT KABUPATEN INDRAGIRI HILIR - jurnalmap map (MAP (Jurnal Manajemen dan Administrasi Publik), 2022)
The purpose of this study was to analyze the effect of employee work goals and work behavior on employee job satisfaction in the Inspectorate of Indragiri Hilir Regency. he unit of analysis in this study is the Inspectorate employee of Indragiri Hilir Regency. The population in this study were all employees of the Inspectorate of Indragiri Hilir Regency as many as 52 people. The sampling technique is total sampling, which is taking a sample from the population. Results of the study and data analysis explained that 1) Partially the work objectives of employees had a significant effect on job satisfaction. 2) Partially work behavior has a significant effect on job satisfaction. 3) Simultaneously employee work goals and work behavior significantly influence job satisfaction. The influence of employee work goals and work behavior on job satisfaction in the Inspectorate of Indragiri Hilir Regency by 57%. While the remaining 43% is explained by other variables not included in this research model.